Handbook of Imagination and Culture - (:unkn) unknown (New York/Oxford: Oxford University Press, 2018)
Imagination allows individuals and groups to think beyond the here-and-now, to envisage alternatives, to create parallel worlds, and to mentally travel through time. Imagination is both extremely personal (for example, people imagine unique futures for themselves) and deeply social, as our imagination is fed with media and other shared representations. As a result, imagination occupies a central position within the life of mind and society. Expanding the boundaries of disciplinary approaches, the Handbook of Imagination and Culture expertly illustrates this core role of imagination in the development of children, adolescents, adults, and older persons today. Bringing together leading scholars in sociocultural psychology and neighboring disciplines from around the world, this edited volume guides readers towards a much deeper understanding of the conditions of imagining, its resources, its constraints, and the consequences it has on different groups of people in different domains of society. Summarily, this Handbook places imagination at the center, and offers readers new ways to examine old questions regarding the possibility of change, development, and innovation in modern society.
Keywords: Imagination; sociocultural psychology; interdisciplinary